1991
DOI: 10.1073/pnas.88.20.9311
|View full text |Cite
|
Sign up to set email alerts
|

Solvent reorganizational red-edge effect in intramolecular electron transfer.

Abstract: Polar solvents are characterized by statistical distributions of solute-solvent interaction energies that result in inhomogeneous broadening of the solute electronic spectra. This allows photoselection of the high interaction energy part of the distribution by excitation at the red (long-wavelength) edge of the absorption bands. We observe that intramolecular electron transfer in the bianthryl molecule from the locally excited (LE) to the charge-transfer (CT) state, which requires solvent relaxation and does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…The concept ofparallel dipole moments between the So and the S; states ofthe flavonols studied is consistent with the fact that the position of the 3-HF PT tautomer fluorescence is Experience in the application of the CT fluorescence of bianthryl (44,45) and also with the PT fluorescence of 4-hydroxy-5-azaphenanthrene (37) in the investigation of different protein binding sites is encouraging. The fluorescence probe DHF combines both the CT and the PT fluorescences in one molecule.…”
Section: Resultsmentioning
confidence: 54%
“…The concept ofparallel dipole moments between the So and the S; states ofthe flavonols studied is consistent with the fact that the position of the 3-HF PT tautomer fluorescence is Experience in the application of the CT fluorescence of bianthryl (44,45) and also with the PT fluorescence of 4-hydroxy-5-azaphenanthrene (37) in the investigation of different protein binding sites is encouraging. The fluorescence probe DHF combines both the CT and the PT fluorescences in one molecule.…”
Section: Resultsmentioning
confidence: 54%
“…It was found that different excited-state reactions in the conditions of slow mobility in the environment of the excited species exhibit strong site selectivity. Among these intramolecular reactions are excited-state isomerizations and also electron and proton transfers (23,24) These low-barrier reactions may be considered as analogues of catalytic and biocatalytic ground-state reactions, and this opens the possibility of studying their dependence on the dynamics of the protein matrix on a fast scale of nuclear motions (25).…”
Section: Introductionmentioning
confidence: 99%
“…The essential criteria for the observation of the red edge effect can therefore be summarized as follows: (a) the fluorophore should normally be polar to be able to suitably orient the neighboring solvent molecules in the ground state (however, molecules such as bianthryl which are nonpolar in the ground state and yet could be polar in the excited state due to intramolecular charge transfer reaction are exceptions to this 28,29 ); (b) the "solvent" molecules (such as water, protein backbone, lipid headgroups) surrounding the fluorophore should be polar; (c) the solvent reorientation time around the excited state dipole should be comparable to or longer than the fluorescence lifetime (this is the most important criterion of REES); and (d) there should be a relatively large change in the dipole moment of the fluorophore upon excitation. In general, the dipole moment of molecules increases upon excitation.…”
Section: Rees: Conceptual Frameworkmentioning
confidence: 99%